REVERSAL BURDEN OF EVIDANCE ON A CRIMINAL CORRUPTION IN INDONESIA - Hasnawati, Hasnawati (Universitas Tadulako, 2018)
The research aim are to know the implementation of strict evidence in corruption committed in Indonesia and the constraint or obstacle faced by the corruption agency. The method of this research was normative juridical, because the research about reversal burden of proof of corruption in crime in Indonesia, which data obtained from primary, secondary, and tertiary legal materials. Research result reveal that implementation of proof in corruption cases is often felt to be ineffective and very burdensome to the Investigator apparatus therefor Â two theories of proof, namely the free theory embraced by the dependent and negative theory according to the law adoptedÂ by the public prosecutor or ordinary commonly called the theory reversal burden ofÂ limited proof and in balance , the dependent has the right to proved that he has not commited a criminal act of corruption and that the prosecutor still has the duty to verify the indictment. The obstacles faced by law enforcement in implementing the burdening system of proof on the handling of corruption crime, namely the Contraints for the public Prosecutor and the obstacle for the judge divided into 2(two) types, namely : Juridical and Non Juridical Contrains